The catalytic potential of high-kappa dielectrics for graphene formation - Scott, A; Dianat, A; Boerrnert, F; Bachmatiuk, A; Zhang, S; Warner, J; Borowiak-Palen, E; Knupfer, M; Buechner, B; Cuniberti, G; Ruemmeli, M (2011)
The growth of single and multilayer graphene nanoflakes on MgO and ZrO 2 at low temperatures is shown through transmission electron microscopy. The graphene nanoflakes are ubiquitously anchored at step edges on MgO (100) surfaces. Density functional theory investigations on MgO (100) indicate C2 H2 decomposition and carbon adsorption at step-edges. Hence, both the experimental and theoretical data highlight the importance of step sites for graphene growth on MgO. © 2011 American Institute of Physics.